Kajian Analisis Aksesibilitas Transportasi Publik di Kawasan Cipete Raya - Tofani Wahyu Saputro; Andyka Kusuma (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to analyze the accessibility of public transportation in the Cipete Raya transit area which is an active trading area planning area. In this context, smooth mobility is an important factor to maintain a sustainable economic cycle. Therefore, it is important to provide effective public transportation facilities and infrastructure around the area. The method used in this study is space syntax analysis, which is used to identify streets that have integration and connectivity. In addition, this study also uses the PTAL (Public Transport Accessibilty Levels) method to evaluate the level of accessibility of public transportation in an area. The results of the study show that there is a relationship between connectivity and integration of routes in the Cipete Raya area. There are several areas in the eastern part that have better public transportation accessibility compared to the western region. This shows the need for improvements in the provision of public transportation in the area in order to create better accessibility such as adding modes of transportation or increasing the frequency of Transjakarta buses.